2021
DOI: 10.1097/adm.0000000000000928
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Hospitalizations for Serious Infections Among People With Opioid Use Disorder in Ontario, Canada

Abstract: Objectives Opioid use among people who inject drugs can lead to serious complications, including infections. We sought to study trends in rates of these complications among people with an opioid use disorder (OUD) and the sequelae of those hospitalizations. Methods We analyzed all inpatient hospitalizations for serious infections (infective endocarditis [IE], spinal infections, nonvertebral bone infections, and skin or soft tissue infections) among people with OUD in Ontari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…As all patients in our study had IDU-IE, we cannot say from these data whether injecting pharmaceutical opioid tablets increases risk for serious bacterial infections more than injecting heroin or fentanyl. While one study identified an association between controlled-release hydromorphone prescriptions and IDU-IE in Ontario [ 64 ], a small minority of patients with IDU-IE in Ontario have recent prescriptions for hydromorphone [ 6 , 64 ]. Increasing rates of serious injection drug use-associated bacterial infections have been observed in many jurisdictions [ 4 , 5 ], and in Ontario appear to parallel transitions in the drug supply towards increasing use of illicitly-manufactured fentanyl [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As all patients in our study had IDU-IE, we cannot say from these data whether injecting pharmaceutical opioid tablets increases risk for serious bacterial infections more than injecting heroin or fentanyl. While one study identified an association between controlled-release hydromorphone prescriptions and IDU-IE in Ontario [ 64 ], a small minority of patients with IDU-IE in Ontario have recent prescriptions for hydromorphone [ 6 , 64 ]. Increasing rates of serious injection drug use-associated bacterial infections have been observed in many jurisdictions [ 4 , 5 ], and in Ontario appear to parallel transitions in the drug supply towards increasing use of illicitly-manufactured fentanyl [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…While one study identified an association between controlled-release hydromorphone prescriptions and IDU-IE in Ontario [ 64 ], a small minority of patients with IDU-IE in Ontario have recent prescriptions for hydromorphone [ 6 , 64 ]. Increasing rates of serious injection drug use-associated bacterial infections have been observed in many jurisdictions [ 4 , 5 ], and in Ontario appear to parallel transitions in the drug supply towards increasing use of illicitly-manufactured fentanyl [ 6 ]. Known risk factors for serious injecting-related infections include more frequent injecting (which has been associated with fentanyl and with stimulants), re-use of contaminated needles and filters, and subcutaneous injecting [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Injection drug use–associated bacterial and fungal infections (e.g., skin and soft-tissue infections, endocarditis, osteomyelitis, septic arthritis, and epidural abscess) are associated with significant morbidity and mortality among people who inject drugs (PWID) and are costly for healthcare systems [ 1 6 ]. The incidence of hospitalization for injecting-related infections is increasing in many parts of the world, including Australia [ 7 ], Canada [ 2 , 8 , 9 ], South Africa [ 10 ], the United Kingdom [ 11 ], the United States of America [ 12 16 ], and India [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Injection drug use-associated bacterial and fungal infections (e.g., skin and soft-tissue infections, endocarditis, osteomyelitis, septic arthritis, and epidural abscess) are associated with significant morbidity and mortality among people who inject drugs (PWID) and are costly for healthcare systems [1][2][3][4][5][6]. The incidence of hospitalization for injecting-related infections is increasing in many parts of the world, including Australia [7], Canada [2,8,9], South Africa [10], the United Kingdom [11], the United States of America [12][13][14][15][16], and India [17].…”
Section: Introductionmentioning
confidence: 99%